Assessment of multi-model climate projections of water resources over South America CORDEX domain - Llopart, Marta [UNESP]; Simões Reboita, Michelle; Porfírio da Rocha, Rosmeri (Springer Nature, 2020)
Future climate projections focusing on precipitation and water resource trends over South America (SA) are investigated using two ensembles. One of them is composed of three global climate models (GCMs), and the other of eight regional climate models (RCMs) from the Coordinated Regional Climate Downscaling Experiment (CORDEX). The present (1970–2005) and the future (2006–2100) climate trends are analyzed for representative pathway scenarios 4.5 (RCP4.5) and 8.5 (RCP8.5). For the most pessimistic scenario (RCP8.5), trends in water resources are assessed considering the terrestrial branch of the hydrologic cycle by analyzing the precipitation minus evapotranspiration (P-ET). For the present climate, RCMs added value to the GCMs in simulating more realistic precipitation fields in several regions. GCMs and RCMs project, in general, the same precipitation change signal for the end of the 21st century over SA, which is stronger in RCP8.5 than in RCP4.5. For RCP8.5 in most regions, GCMs and RCMs ensembles have the same precipitation trend signal, but a great spread between the ensemble members, which is greater in austral summer than winter, can be noted. In winter a negative trend in rainfall in most members and regions predominates. At the end of the 21st century, relative changes in rainfall in RCP8.5 are in the range of +14% (over northeastern Brazil in summer) to − 36% (over the Andes Mountains in winter). In RCP8.5, the ensembles project an increase in air temperature with a similar magnitude, while in RCP4.5 the trends are weaker. For air temperature, there is small spread between members, and the positive trend is statistically significant for all ensemble members in the RCP8.5 scenario. In terms of water resources, on an annual scale, for RCP8.5 the RCM ensemble projects a larger area with wetter conditions in the future than GCMs. Regionally, it is expected a decrease in water availability in the Amazon basin and an increase over northeast Brazil and southeast SA during the summer. In other regions (northern Amazon, the Andes Mountains and Patagonia) the ensembles indicate drier conditions in the future winter, except in southern Amazon. It is expected that such information could be useful for devising adaptation and mitigation policies due to climate change over the SA.
Keywords: Climate projections; CORDEX; South America; Water resources trend, regional and global models